Are null segregants new combinations of heritable material and should they be regulated? - Heinemann, Jack A.; Clark, Katrin; Hiscox, Tessa C.; McCabe, Andrew W.; Agapito-Tenfen, Sarah Z. (Frontiers in Genome Editing, 2023)
Through genome editing and other techniques of gene technology it is possible to create a class of organism called null/negative segregants. These organisms (GMOs) are products of gene technology but are argued to have no lingering vestige of the technology after segregation of chromosomes or deletion of insertions. The argument implies that regulations have no further value because any unique potential to cause harm also has been removed. We tackle this question of international interest by reviewing the early history of the purpose of gene technology regulation. The active ingredients of techniques used for guided mutagenesis, eg site-directed nucleases such as CRISPR/Cas, are promoted for having a lower potential per reaction to create a hazard. However, others see this as a desirable industrial property of the reagents that will lead to genome editing being used more and nullifying the promised hazard mitigation. The contest between views revolves around whether regulation could alter the risks in the responsible use of gene technology. We conclude that gene technology, even when used to make null segregants, has characteristics that make regulation a reasonable option for mitigating potential harm. Those characteristics are that it allows people to create greater harm faster, even if also creating benefits; the potential for harm increases with more use of the technique but safety does not; and regulation can control harm scaling.